The Role of Perceived Usefulness, Perceived Ease of Use, and Task Technology Fit to Increase Perceived Impact on Learning - Aulia, Nur Saskia; Marsasi, Endy Gunanto (SENTRALISASI, 2024)
This study aims to explore Task-Technology Fit, Perceived Usefulness, and Perceived Ease of Use on users' Attitudes toward Video Conferencing applications, as well as their impact on Perceived Impact on Learning. Researchers added Task-Technology Fit as an element of novelty and used the Technology Acceptance Model as the main theory used. This research uses a survey method with the participation of 170 respondents who actively use Video Conference applications in various contexts and are of all ages with productive age specifications. The results of the analysis show that there is a significant positive correlation between Task-Technology Fit and Perceived Usefulness, as well as Task-Technology Fit and Perceived Ease of Use. In addition, a significant positive relationship was detected between Perceived Ease of Use and Perceived Usefulness. Furthermore, Perceived Usefulness and Perceived Ease of Use have a positive impact on users' Attitudes toward Video Conferencing applications. Apparently, user Attitude also has a proven positive influence on the Perceived Impact on Learning. Structural Equation Modeling (SEM) was used as the analysis technique conducted using AMOS Graphics 24. The practical implications of these findings involve recommendations for Video Conferencing application developers to improve features and design to enhance user experience. Hopefully, these findings can support the development of video conferencing-based technologies to be more effective and have a positive impact on virtual learning and interaction.